Executive control, ERP and pro-inflammatory activity in emotionally exhausted middle-aged employees. Comparison between subclinical burnout and mild to moderate depression. (December 2017) - Gajewski, Patrick D.; Boden, Sylvia; Freude, Gabriele; Potter, Guy G.; Claus, Maren; Bröde, Peter; Watzl, Carsten; Getzmann, Stephan; Falkenstein, Michael
Highlights: Burnout and depression are largely overlapping syndromes. Work related questionnaires differentiate between burnout and depression. ERP show specific reduction of preparation, working memory and orienting towards task switch in burnout. Immunological parameters did not differentiate between burnout and depression. IL-6 and IL-12 were associated with burnout severity in male subjects. Abstract: Burnout is a syndrome occurring mainly in individuals with long-term stressful work. The main complaints are emotional exhaustion and reduced performance. Burnout also largely overlaps with depression. Both are characterized by increased incidence of infections due to dysregulation of the immune system, overexpression of pro-inflammatory cytokines and cognitive deficits, particularly related to executive functions. To distinguish between burnout and depression already at the pre-clinical stage, the present double-blinded study compared immunological and cognitive parameters in seventy-six employees from emotionally demanding occupations who were post-hoc subdivided into two groups scoring low (EE−) and high (EE+) in emotional exhaustion and low (DE−) and high (DE+) in depression. Immunological parameters were measured from blood samples. Executive functions were studied by analyzing event-related brain potentials (ERPs) and performance during a task switching paradigm. Psychosocial job parameters were measured with standardized questionnaires. Burnout and mild to moderate depression largely overlapped. However, several subjects showed burnout without depressive symptoms. Higher levels of the pro-inflammatory cytokines IL-6 and IL-12 were correlated with burnout severity and depressive symptoms in male individuals. In the switch task a trend for lower performance in the EE+ vs. EE− group and no difference between DE+ and DE− groups were found. In the ERPs, however, differences were observed which distinguished between subclinical burnout and depression: the terminal contingent negative variation (CNV), indicating preparatory activity and the P3b, related to allocation of cognitive resources were generally reduced in EE+ vs. EE−, whereas no differences were found in the DE+ vs. DE− groups. The frontal P3a was selectively reduced in switch trials in the EE+ vs. EE− group and showed only a trend in DE+ vs. DE−, indicating impairment of executive control in subclinical burnout. Taken together, the results unveil specific immunological changes and declines in brain functions in employees with subclinical burnout that are not apparent in persons with moderate depression. Hence, the combination of immunological, behavioral and ERP methods renders a promising method for distinguishing both syndromes and for improving an early diagnosis of burnout before a clinical stage is reached.